2008
DOI: 10.1016/j.ijsu.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

An integrated laparoscopic simulator (i-Sim™) to develop surgical skills outside the operating theatre: A novel means to improve training facilities in the UK

Abstract: There is a paucity of regular training facilities for MAS in the UK and there was an exceptionally strong agreement among our participants that regular training on laparoscopic simulators would be useful. Additionally, i-Sim offers the possibility of a readily accessible alternative to current training approaches to laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…8 A recent survey of surgeons in the UK has shown that although 93% think access to a laparoscopic simulator would be useful, only 15% had regular access to a simulator for training. 4 The simulator and model we have described in this study can be made by a keen trainee or trainer to practise during time between cases or while on call. If the simulator is left in the theatre coffee room, a trainee could practise while waiting for a patient needing an LA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A recent survey of surgeons in the UK has shown that although 93% think access to a laparoscopic simulator would be useful, only 15% had regular access to a simulator for training. 4 The simulator and model we have described in this study can be made by a keen trainee or trainer to practise during time between cases or while on call. If the simulator is left in the theatre coffee room, a trainee could practise while waiting for a patient needing an LA.…”
Section: Discussionmentioning
confidence: 99%
“…A survey in the north of England of consultants and trainees in urology, general surgery and gynaecology involved with laparoscopic surgery revealed that although 95% felt that simulator training is useful, 40% did not have access to a simulator. 4 The webcam simulator was first described in the literature by an Australian author in 1995. 5 It can be made by an enthusiastic trainee to practise alone at home.The aim of this study was to describe a low-cost model to simulate the LA and assess its face and construct validity in a webcam simulator.…”
Section: Ann R Coll Surg Englmentioning
confidence: 99%
“…Participants rated the simulator highly in terms of satisfaction. This compares favourably with other technical skills simulators [22,23,24]. Investigators in a number of technical skills simulation disciples have reported transference of skills from bench top simulators to a human cadaver model [25] as well as operating theatre environments [26, 27].…”
Section: Discussionmentioning
confidence: 92%
“…Last, traditional laboratory-based skill training is not tailored to individual's needs, and, therefore, does not compensate for differences in innate abilities and enhance potential talents. Those challenges to traditional laboratorybased skills training provide the rationale for integrating such training into clinical programmes (Dhariwal et al 2007 Singh et al 2008). Centralising laboratory-based training for all trainees in a programme onto a single site makes a more systematic and standardised approach possible, provides a larger pool of experts to draw on as trainers and offers economies of scale.…”
Section: Introductionmentioning
confidence: 99%